The impact of soil acidification on cementing substances and aggregate stability - Xiaoxu Zhu; Shengchen Zhao; Siqi Lin; Jihong Wang; Su Leng (PLoS ONE, 2025)
The excessive utilization of chemical fertilizers, particularly nitrogen fertilizers, is leading to decline in the pH level of the black soil in Jilin Province. Acidification of black soil leads to reduced salt base saturation, decreased organic matter content, and increased soil degradation, which, in turn, leads to diminshed aggregate stability and poor soil structure, negatively affecting soil fertility. As a result, the sustainability of food production and farmland ecosystem stability are at risk. The precise relationship between alterations in cementing substances and changes in soil aggregate stability during the acidification of black soil remains unclear, and the ultrasonic thermal difference method allows for the quantitative description of changes in soil aggregate stability. Therefore, this study employed the ultrasonic thermal difference method to investigate the impact of acidification on the stability of black soil aggregates and their cementing substances through a simulated fertilizer drenching experiment, thus elucidate the relationship between primary cementing materials and the stability of aggregates under varying degrees of black soil acidification, and to provides theoretical basis and data for alleviating and preventing acidification of black soil in Jilin Province. The results disclosed a gradual decline in soil organic carbon (SOC) levels during the acidification experiment, while water-soluble organic carbon (WSOC) first increased and then decreased. After 25 years of simulated leaching, SOC decreased by 1.34% and WSOC declined by 15.63%. Acidification has a minimal impact on Fe-Al bonded organic carbon but significantly reduces calcium-bonded organic carbon by 17.07% over 25 years. The content of exchangeable Ca2+ and Mg²⁺ decreases as acidification intensifies. After 25 years, exchangeable Ca2+ and Mg²⁺ decreased by 9.42% and 7.00%, respectively. The acidification of the test soil resulted in a 46.5% reduction in the aggregate stability energy (E) of water-stable microaggregates, with an average decrease of 14.04 J/g for every 0.1 unit decrease in pH. Additionally, the soil critical stabilization energy (Ecrit) exhibited a 51.48% reduction. The results demonstrated that a decrease of 0.32 J/g in E was associated with a 0.1 unit decrease in pH on average. Furthermore, the multivariate linear regression analysis revealed that the reduction in soil organic carbon (SOC) content contributed the most to the decline in E, followed by Calcium bond-bound soil organic carbon (Ca-SOC). Notably, Ca-SOC exerted the greatest influence on the reduction in sand grain Ecrit, followed by SOC.